Accurate MTF measurement in digital radiography using noise response - Kuhls-Gilcrist, Andrew; Jain, Amit; Bednarek, Daniel R.; Hoffmann, Kenneth R.; Rudin, Stephen (Medical physics (Lancaster), 2010)
Purpose: The authors describe a new technique to determine the system presampled modulation transfer function (MTF) in digital radiography using only the detector noise response. Methods: A cascaded-linear systems analysis was used to develop an exact relationship between the two-dimensional noise power spectrum (NPS) and the presampled MTF for a generalized detector system. This relationship was then utilized to determine the two-dimensional presampled MTF. For simplicity, aliasing of the correlated noise component of the NPS was assumed to be negligible. Accuracy of this method was investigated using simulated images from a simple detector model in which the “true” MTF was known exactly. Measurements were also performed on three detector technologies (an x-ray image intensifier, an indirect flat panel detector, and a solid state x-ray image intensifier), and the results were compared using the standard edge-response method. Flat-field and edge images were acquired and analyzed according to guidelines set forth by the International Electrotechnical Commission, using the RQA 5 spectrum. Results: The presampled MTF determined using the noise-response method for the simulated detector system was in close agreement with the true MTF with an averaged percent difference of 0.3% and a maximum difference of 1.1% observed at the Nyquist frequency ( f N ) . The edge-response method of the simulated detector system also showed very good agreement at lower spatial frequencies (less than 0.5